Fires in Amazonian Blackwater Floodplain Forests: Causes, Human Dimension, and Implications for Conservation - Carvalho, Tayane Costa; Wittmann, Florian; Piedade, Maria Teresa Fernandez; Resende, Angélica Faria de; Silva, Thiago Sanna Freire; Schöngart, Jochen (Frontiers in Forests and Global Change, 2021)
The Amazon basin is being increasingly affected by anthropogenic fires, however, most studies focus on the impact of fires on terrestrial upland forests and do not consider the vast, annually inundated floodplains along the large rivers. Among these, the nutrient-poor, blackwater floodplain forests (igapós) have been shown to be particularly susceptible to fires. In this study we analyzed a 35-year time series (1982/1983-2016/2017) of Landsat Thematic Mapper from the Jaú National Park (Central Amazonia) and its surroundings. Our overall objective was to identify and delineate fire scars in the igapó floodplains, and relate the resulting time-series of annual burned area to the presence of human populations and interannual variability of regional hydroclimatic factors. We estimated hydroclimatic parameters for the study region using ground-based instrumental data (maximum monthly temperature–Tmax, precipitation–P, maximum cumulative water deficit–MCWD, baseflow index–BFI, minimum water level–WLmin90 of the major rivers) and large-scale climate anomalies (Oceanic Niño Index–ONI), considering the potential dry season of the non-flooded period of the igapó floodplains from September to February. Using a wetland mask, we identified 518,135 ha of igapó floodplains in the study region, out of which 17,524 ha (3.4%) burned within the study period, distributed across 254 fire scars. About 79% of the fires occurred close to human settlements (<10 km distance), suggesting that human activities are the main source of ignition. Over 92.4% of the burned area is associated with El Niño. Non-linear regression models indicate highly significant relationships (p<0.001) with hydroclimatic parameters, positive with Tmax (R²adj.=0.83) and the ONI (R²adj.=0.74) and negative with P (R²adj.=0.88), MCWD (R²adj.=0.90), WLmin90 (R²adj.=0.61) and BFI (R²adj.=0.80). Hydroclimatic conditions were of outstanding magnitude in particular during the El Niño event in 2015/2016, which was responsible for 42.8% of the total burned floodplain area. We discuss these results under a historical background of El Niño occurrences and a political, demographic, and socioeconomic panorama of the study region considering the past 400 years, suggesting that disturbance of igapós by fires is not a recent phenomenon. Concluding remarks focus on current demands to increase the conservation to prevent and mitigate the impacts of fire in this vulnerable ecosystem.